Leader Unethical Pro-Organizational Behavior and Employee Unethical Conduct: Social Learning of Moral Disengagement as a Behavioral Principle - Lian, Huiwen; Huai, Mingyun; Farh, Jiing-Lih; Huang, Jia-Chi; Lee, Cynthia; Chao, Melody M. (Journal of management, 2022)
Unethical behavior in organizations has attracted much attention among researchers, yet we know little about when and why unethical behavior conducted by leaders that is intended to benefit the organization—or leader unethical pro-organizational behavior (UPB)—might translate into employee unethical behavior. Drawing on a social-learning-of-principle perspective, which proposes that people can learn the principles that govern observed behaviors, we propose that employees, especially those with a high power distance orientation, can abstract and learn a moral disengagement behavioral principle by observing leader UPB. This learned moral disengagement behavioral principle then enables them to engage in unethical behaviors that may be intended to benefit or harm their organizations. In two multiwave field studies with data collected from real estate agents, we found overall support for our theoretical model but the moderating effect of power distance orientation. We discuss some key theoretical and practical implications of these findings.